IMPLEMENTASI MANAJEMEN ARSIP DIGITAL DALAM MENINGKATKAN EFISIENSI ADMINISTRASI PERKANTORAN DI PT. JEPE PRESS MEDIA UTAMA - Zelda Agustina Safitri; Durinta Puspasari (STKIP Pesisir Selatan, 2026)
Digital archival management is an important element in supporting the effectiveness of office administration in the modern era. The transformation from a manual archive system to an electronic archive provides significant changes in the process of storing as well as managing documents. PT. Jepe Press Media Utama Surabaya is the object of this research. The focus of this research is to understand the management of digital archives used by PT. Jepe Press Media Utama Surabaya. This type of research is descriptive research. Data collection techniques use questionnaires and interviews, while the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The research results show that: 1) The availability of electronic records has been supported by digital storage facilities and systems that are easily accessible to employees, 2) The use of digital records provides substantive benefits in the form of increased efficiency in document tracing and savings in physical storage space, 3) The majority of employees are able to operate the digital archive system well, even though there are still certain technical obstacles, such as storage limitations.